The PID Odyssey 2030: outlooks, unmet needs, hurdles, and opportunities — proceedings from the IPOPI global multi-stakeholders’ summit (June 2022) - Tadros, Susan; Prévot, Johan; Meyts, Isabelle; Sánchez-Ramón, Silvia; Erwa, Nahla H.; Fischer, Alain; Lefevre, Guillaume; Hotchko, Matthew; Jaworski, Peter M.; Leavis, Helen; Boersma, Cornelis; Drabwell, Jose; et al. (Frontiers in Immunology, 2023)
IPOPI held its first Global Multi-Stakeholders’ Summit on 23-24 June 2022 in Cascais, Portugal. This IPOPI initiative was designed to set the stage for a stimulating forward-thinking meeting and brainstorming discussion among stakeholders on the future priorities of the PID community. All participants were actively engaged in the entire Summit, bringing provocative questions to ensure a high level of discussion and engagement, and partnered in identifying the outlooks, unmet needs, hurdles and opportunities of PIDs for 2030. The topics that were covered include diagnosis (e.g., newborn screening [NBS], genomic sequencing— including ethical aspects on the application of genomics on NBS, the role of more accurate and timely diagnostics in impacting personalized management), treatment (e.g., the therapeutic evolution of immunoglobulins in a global environment, new therapies such as targeted therapies, new approaches in curative therapies), the interactions of Primary ID with Secondary ID, Autoinflammatory Diseases and other diseases as the field experiences an incessant evolution, and also the avenues for research in the field of humanities and human sciences such as Patient-Reported Outcome Measures (PROMs), Patient-Reported Experience Measures (PREMs), and Health-Related Quality Of Life (HRQoL). During this meeting, all participants contributed to the drafting of recommendations based on our common understanding of the future opportunities, challenges, and scenarios. As a collection of materials, perspectives and summaries, they are succinct and impactful and may help determine some of the next key steps for the PID community.